Contemporaneous Risk Factors for Visual Acuity in Non-Infectious Uveitis. (18th August 2021) - Pistilli, Maxwell; Gangaputra, Sapna S.; Pujari, Siddharth S.; Jabs, Douglas A.; Levy-Clarke, Grace A.; Nussenblatt, Robert B.; Rosenbaum, James T.; Sen, H. Nida; Suhler, Eric B.; Thorne, Jennifer E.; Bhatt, Nirali P.; Foster, C. Stephen; et al.
ABSTRACT: Introduction: We evaluated the associations of clinical and demographic characteristics with visual acuity (VA) with over 5 years in a subspecialty noninfectious uveitis population. Methods: Retrospective data from 5, 530 noninfectious uveitis patients were abstracted by expert reviewers, and contemporaneous associations of VA with demographic and clinical factors were modeled. Results: Patients were a median of 41 years old, 65% female, and 73% white. Eyes diagnosed ≥5 years prior to cohort entry had worse VA (−1.2 lines) than those diagnosed <6 months prior, and eyes with cataract surgery performed prior to entry had worse VA (−5.9 lines) than those performed during follow-up. Vitreous haze (−4.2 lines for 3+ vs quiet), hypotony (−2.5 lines for ≤5 mm Hg vs 6–23 mm Hg), and CNV (−1.8 lines) all were strongly associated with reduced VA. Conclusion: Factors associated with reduced VA included well-known structural complications, and lack of subspecialty care during cataract surgery.